2013
DOI: 10.4236/ajps.2013.41018
|View full text |Cite
|
Sign up to set email alerts
|

Protein Profiles and Dehydrin Accumulation in Some Soybean Varieties (<i>Glycine max</i> L. Merr) in Drought Stress Conditions

Abstract: Drought is one of environmental stresses which the most limiting to plant growth and productivity. Drought stress led to a series of changes including biochemical changes like accumulation of osmolit and specific proteins involved in stress tolerance. One of the proteins that play a role in the mechanism of drought resistance is dehydrin protein. This study aimed to identify the protein profiles and dehydrin accumulation in 7 varieties of local Indonesian soybeans: Tanggamus, Nanti, Seulawah and Tidar (toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…Water deficit stress do led to a series of changes including biochemical alterations like accumulation of osmolytes and specific proteins involved in stress tolerance [ 3 ]. One of the proteins that play a role in the mechanism of drought resistance is the LEA types of protein known as dehydrin [ 4 ]. In cotton production, drought is the main abiotic stress responsible for plant growth compromise and severe yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Water deficit stress do led to a series of changes including biochemical alterations like accumulation of osmolytes and specific proteins involved in stress tolerance [ 3 ]. One of the proteins that play a role in the mechanism of drought resistance is the LEA types of protein known as dehydrin [ 4 ]. In cotton production, drought is the main abiotic stress responsible for plant growth compromise and severe yield loss.…”
Section: Introductionmentioning
confidence: 99%
“…Acumulación de proteínas LEA (Welin et al, 1994), principalmente las dehidrinas (Arumingtyas et al, 2013); elongación radicular disminuida, reducción del área foliar (Hu y Xiong, 2014); cierre de estomas (Froux et al, 2005).…”
Section: Deficiencia Hídricaunclassified
“…Dehydrins (DHNs) are plant-specific proteins that accumulate during the abiotic stress that cause cellular dehydration, such as drought, salinity, freezing, or by treatment with the phytohormone ABA 2 . Transcriptional and proteomic studies of abiotic tolerance in several plant species have demonstrated that DHNs transcripts and protein levels increase in tolerant varieties 3 5 . In addition, transgenic studies have widely demonstrated the positive effect of DHNs expression and accumulation in order to survive to changing conditions 6 8 .…”
Section: Introductionmentioning
confidence: 99%